Pre-hospital blood transfusion - an ESA survey of European practice - Thies, Karl-Christian; Truhlář, Anatolij; Keene, Damian; Hinkelbein, Jochen; Rützler, Kurt; Brazzi, Luca; Vivien, Benoît (Scandinavian journal of trauma, resuscitation and emergency medicine, 2020)
BACKGROUND: Blood products are a lifesaving commodity in the treatment of major trauma. Although there is little evidence for use of pre-hospital blood products (PHBP) in seriously injured patients, an increasing number of emergency medical services have started using PHBP for treatment of major haemorrhage. The primary aim of this survey was to establish the degree of prehospital blood product use throughout Europe and discover main indications. The secondary aim was to evaluate opinions about PHBP and also the experience and the personal views of its users. METHODS: The subcommittee for Critical Emergency Medicine of the European Society of Anaesthesiology (ESA) held an online survey of European Helicopter Emergency Services (HEMS) and all French Services d'Aide Médicale Urgente (SAMU) regions. It contained 13 questions both open and multiple-choice about the frequency transfusions are carried out, the PHBP used and the perceived benefit. The survey was distributed to the corresponding HEMS leads in 14 European countries. RESULTS: In total there were 172 valid responses; overall 48% of all respondents have prehospital access to packed red cells, 22% to fresh plasma and 14% use lyophilised plasma. Besides blood product administration, 94% of all services use tranexamic acid. Sixty five percent of all replies came from French and from German services (37 and 28% respectively). PHBP were mainly used for trauma related emergencies. France has the highest uptake of use of blood products at 89%, whereas the rate in Germany was far lower at 6%. Fifty five percent of the service leads felt that PHBP are beneficial, and even lifesaving in individual cases despite being needed infrequently. CONCLUSIONS: We found remarkable dissimilarities in practice between the different European countries. Even if there is not an absolute consensus amongst providers on the benefit of PHBP, the majority feel they are beneficial. The difference in practice is possibly related to the perceived lack of evidence on prehospital blood transfusion. We suggest to include the use of PHBP in trauma registries in order to consolidate the existing evidence.
Keywords: Transfusion; urgentní zdravotnické služby; Trauma; Emergency Medical Services; Blood Transfusion; Hemorrhage; antifibrinolytika; kyselina tranexamová; Europe; Emergency medical services; Tranexamic Acid; Prehospital care; průzkumy a dotazníky; krevní transfuze; Treatment; krvácení; Evropa; lidé; Humans; Surveys and Questionnaires; Antifibrinolytic Agents